Evaluasi Pengaruh Geometri Jalan Angkut Batukapur Terhadap Produksi di Area 242 Bukit Tajarang PT. SEMEN PADANG - Wahyu Rijal Waskito Putra; Yoszi Mingsi Anaperta (Journals Mining Engineering : Bina Tambang, 2020)
Abstract. PT. Semen Padang as a pioneer of the cement industry in Indonesia since 1910 and one of the largest producers for the Sumatra region is trying to increase its production. PT. Semen Padang uses a series of excavators backhoe and dump trucks to move material from the loading point to the Crusher. One of the mining activities affecting production is hauling operations. Factors that can affect transportation activities are the geometry of the haul road. High road grade results in a loaded conveyance which cannot run at optimal speed while a narrow width of the haul road will result in the opposite direction of conveyance which will prioritize one of the conveyances for the road first, this will cause the conveyance distribution time to be longer while loading. The condition of the mining road at PT. Semen Padang is not in accordance with AASHTO standards. There are slopes that are not up to standard as many as 14 segments with a value of 12.96% and 15.19% while according to AASHTO the suitable cross slope is 8% -10%. The researcher will re-evaluate the geometry of the PT Semen Padang mine road and assess the Total Resistance.Keyword: Geometry, Slope, PT. Semen Padang, Production, Grade.